2015
DOI: 10.1007/s40145-015-0162-0
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the phase space in lead-free (K x Na1-x )1-y Li y (Nb1-z Ta z )O3 ferroelectric ceramics

Abstract: A library of ceramic compounds based on the lead-free (K x Na 1x ) 1y Li y (Nb 1z Ta z )O 3 solid solution has been synthesized and characterized using high-throughput experimentation (HTE) method. The phase space previously reported by Saito and Takao has been expanded to {{x, 0.1, 1.0}, {y, 0, 0.1}, {z, 0, 0.2}}, and new phase boundaries are observed. The relative density values show that with the appropriate sintering temperature, ~92% of the theoretical density can be reached. The relative permittivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Of the three KNN-based ceramics, KNN compositions have the lowest dielectric constant values followed by KNNLT compositions and finally KNNLST compositions. It has been reported that with isovalent element substitutions in KNN ceramics, both the sinterability and properties of the ceramics is improved [2,7,41]. The contributions to dielectric polarization in this case are possibly by electron shift within the molecules, the rotating dipolar molecules and/or the changing of ion places in the lattice.…”
Section: Dielectric Propertiesmentioning
confidence: 90%
“…Of the three KNN-based ceramics, KNN compositions have the lowest dielectric constant values followed by KNNLT compositions and finally KNNLST compositions. It has been reported that with isovalent element substitutions in KNN ceramics, both the sinterability and properties of the ceramics is improved [2,7,41]. The contributions to dielectric polarization in this case are possibly by electron shift within the molecules, the rotating dipolar molecules and/or the changing of ion places in the lattice.…”
Section: Dielectric Propertiesmentioning
confidence: 90%